Rationale for Implementation of Warm Cardiac Surgery in Pediatrics - Durandy, Yves (Frontiers in Pediatrics, 2016)
Cardiac surgery was developed thanks to the introduction of hypothermia and cardiopulmonary bypass in the early 1950s. The deep hypothermia protective effect has been essential to circulatory arrest complex cases repair. During the early times of open-heart surgery, a major concern was to decrease mortality and to improve short-term outcomes. Both mortality and morbidity dramatically decreased over a few decades. As a consequence, the drawbacks of deep hypothermia, with or without circulatory arrest, became more and more apparent. The limitation of hypothermia was particularly evident for the brain and regional perfusion was introduced as a response to this problem. Despite a gain in popularity, the results of regional perfusion were not fully convincing. In the 1990s, warm surgery was introduced in adults and proved to be safe and reliable. This option eliminates the deleterious effect of ischemia reperfusion injuries through a continuous, systemic coronary perfusion with warm oxygenated blood. Intermittent warm blood cardioplegia was introduced later, with impressive results. We were convinced by the easiness, safety and efficiency of warm surgery and shifted to warm pediatric surgery in a two-step program. This article outlines the limitations of hypothermic protection and the basic reasons that led us to implement pediatric warm surgery. After tens of thousands of cases performed across several centers, this reproducible technique proved a valuable alternative to hypothermic surgery.